2013
DOI: 10.3109/09273948.2013.841495
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Selected Biomarkers, Polymorphisms, and Clinical Features for Oligoarticular Juvenile Idiopathic Arthritis-associated Uveitis

Abstract: An age-associated risk of uveitis was observed in children younger than 3 years at the time of JIA onset. ESR values at arthritis onset higher than 22 mm/h were also related to uveitis development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Apart from demographic and clinical data, further biomarkers to predict uveitis risk for an individual patient are highly desirable. Interestingly, ESR has been shown to correlate well with the risk for uveitis . In our study, an ESR >35 mm/hour at first documentation was associated with a significantly higher risk for uveitis onset during followup (OR 2.0, P < 0.001; univariate analysis) (Table ).…”
Section: Discussionmentioning
confidence: 50%
“…Apart from demographic and clinical data, further biomarkers to predict uveitis risk for an individual patient are highly desirable. Interestingly, ESR has been shown to correlate well with the risk for uveitis . In our study, an ESR >35 mm/hour at first documentation was associated with a significantly higher risk for uveitis onset during followup (OR 2.0, P < 0.001; univariate analysis) (Table ).…”
Section: Discussionmentioning
confidence: 50%
“…Four previous studies examined the relationship between ESR and the occurrence of uveitis in patients with JIA. 4,10,17,18 Elevated ESR appeared to be predictive in 3 of these previous retrospective studies as well. Statistically, these studies found significantly more elevated ESR values of > _35 mm in patients with uveitis…”
Section: Discussionmentioning
confidence: 68%
“…This is the second study demonstrating an elevated ESR to be predictive after adjusting for other predictors in a larger study population. 18 One study described ESR as not having a significant influence on the occurrence of uveitis according to multivariate analysis. 4 Patients diagnosed with uveitis prior to the onset of JIA were not excluded from this study, which might explain this contrasting outcome.…”
mentioning
confidence: 99%
“…Furthermore, our study gave new insight into the role of clinical activity scores and biomarkers (e.g., ESR and S100A12) as prognostic markers for uveitis in JIA. In 4 previous studies, elevated ESR predicted uveitis manifestations , while this was only true for the ERA subgroup of JIA in another study from a German cohort . It may be speculated that a high ESR correlates with the activity of autoimmune processes in JIA, potentially under the influence of Treg cells .…”
Section: Discussionmentioning
confidence: 83%
“…An elevated erythrocyte sedimentation rate (ESR) may indicate activity of an autoimmune disease. Indeed, previous studies indicated an elevated risk of uveitis in JIA patients with an elevated ESR , while no such correlation was found in others . For other factors (e.g., C‐reactive protein [CRP]), no correlation with uveitis risk in JIA has been found previously .…”
mentioning
confidence: 95%